Impact of CMS coverage decision on access to transcatheter aortic valve replacement. Issue 1 (6th February 2014) - O'Neill, Brian P.; O'Neill, William W.; Williams, Donald; Cohen, Mauricio G.; Heldman, Alan W.; Macon, Conrad; Martinez, Claudia A.; Alfonso, Carlos E.; Clark, Pedro Martinez; Velasquez, Omaida; Seo, David; Clermont, Pascal Goldschmidt; et al.
Abstract : Objectives: To assess the impact of the Centers for Medicare and Medicaid Services (CMS) national coverage determination (NCD) on access for patients with aortic stenosis (AS) with transcatheter aortic valve replacement (TAVR) in a tertiary care center. Background: TAVR has given hope to patients with AS who are deemed inoperable. The effects of the NCD on access to patients with AS has not been evaluated. Materials and Methods: A total of 94 inoperable AS patients were evaluated and treated from December 2011 through June of 2012 with TAVR. Patients who underwent transfemoral (TF) vs. non‐TF access were compared. The CMS NCD was released on May 1, 2012 and on July 1, 2012, the nontransfemoral access program was put on hold due to lack of reimbursement. Results: Patients in the TF ( n = 33) and non‐TF access ( n = 61) groups were similar in age (85.2 ± 6.3 vs. 84.8 ± 6.6 P = 0.74) and STS mortality (9.38 ± 5.33 vs. 7.91 ± 3.69, P = 0.074). The iliofemoral arteries were larger diameter in the TF group (7.72 ± 1.49 vs. 6.21 ± 1.78, P < 0.001) and males (7.39 ± 1.81 vs. 6.1 ± 1.61 P < 0.001). More women underwent valve implantation via non‐TF access (73 vs. 23%, P = 0.03). After the NCD, 21 patients who previously qualified for non‐TF TAVR would not be reimbursed by CMS. Four died soon after. Conclusions: After the NCD, the proportion of inoperable patients with severe AS that can be treated with TAVR was greatly reduced due the lack of reimbursement for TAVR via non‐TF access. This effect is particularly pronounced in women. © 2014 Wiley Periodicals, Inc.